CORRELATION PERCEPTION ABOUT THE PROFESSIONALISM OF TEACHERS AND COMMUNICATION CLIMATE WITH THE PERFORMANCE OF TEACHERS MADRASAH AMAL BAKTI 2 HELVETIA DELI SERDANG - Mariatun, Candra Wijaya, Edi Saputra (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2019)
Abstract: The Correlations Perception of Teaching and Teacher Professionalism Against ClimateCommunication with Teacher Performance Madrasah Persatuan Amal Bakti 2 Helvetia Deli Serdang.Thesis : Graduate Program, State University of Islamic North Sumatera Medan, 2019. This studyaimed to determine: (1) the correlations the teacher’s perception of the professionalism of teacherwith teacher performance, (2) communication of climate relationship with teacher performance,and (3) perceptions of teachers to teacher professionalism and communication climate togetherwith teacher performance. The method used in this research is descriptive method with this type ofresearch is correlational research because of the relationship between the study variables. Thepopulation in this study were all teachers who teach in Madrasah Persatuan Amal Bakti 2 HelvetiaDeli Serdang totaling 126 people. Determination of the sample in this study using the nomogramHerry King with an error rate of 5%, and assisted with Table Isaac and Michael, the sample size inthis study were as many as 95 people. Data collection instrument was a questionnaire and thetechnique used is regression analysis and correlation. The findings of this study are: (1) there is asignificant correlations between the perception of teachers on Teacher Professionalism with teacherperformance is indicated by a correlation of 0.711 with the equation of the regression line v =47,305 + 0,3086 X 1 ; (2) there is a significant correlations between climate communication withteacher performance is indicated by the correlation coefficient of 0.541 the equation of the regressionline v = 46,168 + 0,396 X 2 ; (3) there is a significant relationship between teachers’ perceptionsof the professionalism of the Teaching and Climate Communication together with teacher performance,demonstrated by multiple correlation coefficient Ry.12 = 0.767 with the regression line equation.v = 11,65 + 0,136X 1 + 0,218X 2 . The coefficient of determination shows the results of 0.589 thismeans 58.9% of the variation that affects the teacher’s performance can be explained by the perceptionof teachers on Teacher Professionalism and Climate Communication. Based on the findings in thisstudy, the teachers need to perceive the Teacher Professionalism in Teaching Professionalism positivebecause at its core is the assistance provided to all school staff to develop teaching and learningsituations better. Furthermore, the teacher is expected to be able to manage their emotions toimprove communication climate that will ultimately improve their performance.